MAL Inhibits the Production of HIV-1 Particles by Sequestering Gag to Intracellular Endosomal Compartments - Miyakawa, Kei; Nishi, Mayuko; Jeremiah, Sundararaj Stanleyraj; Morikawa, Yuko; Ryo, Akihide (Frontiers in Virology, 2022)
The host innate immune response is the first line of defense against human immunodeficiency virus (HIV) infection. The type I interferon (IFN) response is a robust anti-viral response that induces the transcription of several IFN-stimulated genes (ISGs). However, the effects of ISGs, particularly on the HIV-1 Gag protein, remain largely unknown. Hence, we screened ISG-encoded proteins by bioluminescence resonance energy transfer to identify the crucial host effectors that suppressed Gag function. Consequently, we identified the transmembrane protein MAL as a Gag-interacting ISG product. In fact, ectopic expression of MAL substantially inhibited the production of HIV-1 particles, leading to the translocation, accumulation, and eventual lysosomal degradation of Gag in the host endosomal compartments. Owing to the conserved N-terminal region of MAL, which specifically interacts with HIV-1 Gag, this particular antiviral function of MAL targeting Gag is also conserved among orthologs of various animal species. Notably, the antiviral activity of MAL was partially antagonized by the viral accessory protein Nef, as it interfered with the interaction between MAL and Gag. Therefore, this study reveals a previously unidentified antiviral function of MAL and its viral counteraction. It also sheds new light on therapeutic strategies against HIV-1 infection based on the intrinsic antiviral immunity of host cells.